Hydrogen Gas Therapy: From Preclinical Studies to Clinical Trials - Sano, Motoaki; Tamura, Tomoyoshi (Current Pharmaceutical Design, 2021)
Background: Mounting evidence indicates that hydrogen gas (H2) is a versatile therapeutic agent, even at very low, non-combustible concentrations. The Chinese National Health and Medical Commission recently recommended the use of inhaled H2 in addition to O2 therapy in the treatment of COVID-19-associated pneumonia, and its effects extend to anti-tumor, anti-inflammatory and antioxidant actions. Summary: In this review, we have highlighted key findings from preclinical research and recent clinical studies demonstrating that H2 reduces the organ damage caused by ischemia-reperfusion. We have also outlined the critical role this effect plays in a variety of medical emergencies, including myocardial infarction, hemorrhagic shock, and out-of-hospital cardiac arrest, as well as in organ transplantation. H2 is compared with established treatments such as targeted temperature management, and we have also discussed its possible mechanisms of action, including the recently identified suppression of TNF-α-mediated endothelial glycocalyx degradation by inhaled H2. In addition, our new method that enables H2 gas to be easily transported to emergency settings and quickly injected into an organ preservation solution at the site of donor organ procurement have been described. Conclusion: H2 is an easily administered, inexpensive and well-tolerated agent that is highly effective for a wide range of conditions in emergency medicine, as well as for preserving donated organs.
Keywords: Myocardial infarction